Humanity-Centered Understanding on Health Communication in the Process of Digitalization: A Review of the Proceedings of the 6th MHM International Conference - Li, Zhenyi; Xu, Jing (The Journal of Medicine, Humanity and Media, 2023)
Before every MHM conference, we suddenly hesitate: should we continue to hold it, after all, with more and more conferences focused on "health communication", will MHM be overshadowed? However, after each MHM conference, we felt that it was necessary to persevere, because the papers we received not only focused on the topic of "health communication", but more importantly, echoed the theme of MHM, that is, "humanity research on the impact of ’medicine’ and ’media’ on ’health communication’". This MHM structure (Medicine-Humanity-Media) is rarely discussed in other conferences, but our previous attendees, whether it is the keynote speeches of the guests, the discussions in the sub-sessions, or even the poster papers on the panels, echo and delve into this structure. Therefore, we cherish the efforts made every year, and in 2023 we created the Journal of MHM (JMHM) to publish and document the results of the MHM conference, and at the same time promote the contribution of the MHM structure to health communication research. The articles and abstracts included in this issue of JMHM are all from the 6th MHM International Symposium 2023.